2018
DOI: 10.1159/000488496
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Microvascular Abnormalities Detected by Wide-Field Fluorescein Angiography in Eyes with Branch Retinal Vein Occlusion

Abstract: Purpose: To evaluate the location of microvascular abnormalities using wide-field fluorescein angiography (WFFA) and investigate the impact on visual outcome in eyes with branch retinal vein occlusion (BRVO). Methods: Forty eyes of 39 patients (24 males and 15 females with an average age of 71 years) were retrospectively reviewed. One patient had BRVO bilaterally. WFFA was performed in all patients to evaluate perfusion status and detect microvascular abnormalities. The WFFA images were divided into 3 zones: z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 7 publications
(8 reference statements)
1
12
0
Order By: Relevance
“…In the BRVO study by Yasuda et al 5 on 40 eyes, NVE was more commonly observed in eyes with larger nonperfused retina in the posterior pole than in mid-periphery, but not observed in the far-peripheral retina in their cohort. 5 However, our observations are consistent with Prasad et al 10 in reporting NVE development in untreated or under-treated nonperfusion retina at any location of retina. 10 In the present cohort, the location of NVE is primarily confined to an area of persistent (or residual) black-RI defined by the initial BRVO occlusion territory boundary, which may or may not affect the macula or the far-peripheral retina.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the BRVO study by Yasuda et al 5 on 40 eyes, NVE was more commonly observed in eyes with larger nonperfused retina in the posterior pole than in mid-periphery, but not observed in the far-peripheral retina in their cohort. 5 However, our observations are consistent with Prasad et al 10 in reporting NVE development in untreated or under-treated nonperfusion retina at any location of retina. 10 In the present cohort, the location of NVE is primarily confined to an area of persistent (or residual) black-RI defined by the initial BRVO occlusion territory boundary, which may or may not affect the macula or the far-peripheral retina.…”
Section: Discussionsupporting
confidence: 93%
“… 6 – 9 In contrast, published data on ARI are very limited in BRVO, and the studies available had applied ARI of 5 DD or more as the arbitrary guide for NVE risk in ischemic BRVO. 1 , 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Retinal neovascularization also developed at the borders between the nonperfused and perfused areas in eyes with BRVO. 29 It is well known that overexpression of vascular endothelial growth factor (VEGF) in eyes with ischemic retinal diseases causes retinal neovascularization. MAs also formed after intravitreal injection of VEGF proteins in nonhuman primates, 30 and blockage of VEGF suppressed MA formation in eyes with BRVO.…”
Section: Discussionmentioning
confidence: 99%